Application of genetic algorithms to optimize distribution in food transport companies: a systematic literature review - Ayre Rosales, Dylan Anndrei (2024)
The article applies genetic algorithms as a tool of artificial intelligence that provides optimal solutions to the problem of vehicle routing in the distribution chain by transport companies. The main problem in the food sector is transporting perishable goods with low life expectancy. The methodology used for the present work was a systematic literature review focused on applying genetic algorithms in transport companies. To achieve this goal, a massive search was made in Scopus, Web of Science, and Proquest databases. A total of 60 articles were compiled for this document. For the study of the extracted articles, they were categorized into three factors: total costs in distribution, profitability, and delivery times. For the findings section, the use of Vosviewer software was used. The use of this software allowed us to demonstrate that genetic algorithms would have a positive influence on each of the factors mentioned